MANEJO DA IRRIGAÇÃO E ADUBAÇÃO NITROGENADA NO FEIJOEIRO - CULTIVAR BRS ESTILO - KLIP, Dioph Vitor de Oliveira,; LOPES, Adriano da Silva,; FRANCO, Jhonatan da Silva,; KRAESKI, Marcos Jeeferson,; LOPES, Rafael da Silva,; SILVA, Davi Pessoa, (ANAIS DO ENIC, 2025)
-